Optimalisasi Timbangan Beras Otomatis menggunakan Arduino IoT Cloud - Julianti Habibuddin; Muhammad Alif; Ruslan; Renaldi Halimsyah; Muhammad Ariyanto Arifuddin (Jurnal Fokus Elektroda : Energi Listrik, Telekomunikasi, Komputer, Elektronika dan Kendali), 2023)
This research aims to optimize an automatic rice weighing system by utilizing iot (internet of things) technology through the arduino iot cloud platform. Previous research had designed a digital scale using an lcd touchscreen as input and an arduino uno as the microcontroller. This study takes an approach to optimize the microcontroller by utilizing the nodemcu esp32, capable of connecting to the iot platform, namely the arduino iot cloud. The hardware setup comprises an lcd touchscreen, a load cell sensor, the node mcu esp32 microcontroller, and a servo. The software component requires an internet connection to display the measurement results on the arduino iot cloud platform. The measurement results on Arduino IoT Cloud for a weight of 1000 grams show an average accuracy of 99.10%. Meanwhile, for a weight of 2000 grams, the average accuracy is 99.63%, and for a weight of 3000 grams, the average accuracy is 99.87%.